Two‐Year Mortality in Homebound Older Adults: An Analysis of the National Health and Aging Trends Study. Issue 1 (19th September 2016) - Soones, Tacara; Federman, Alex; Leff, Bruce; Siu, Albert L.; Ornstein, Katherine
Abstract : Objectives: To determine the association between homebound status and mortality. Design: Cross‐sectional. Setting: Annual, in‐person interviews. Participants: A nationally representative sample of community‐dwelling, Medicare beneficiaries aged 65 and older enrolled in the National Health and Aging Trends Study between 2011 and 2013 (N = 6, 400). Measurements: Two‐year mortality and prevalence of homebound status in the year before death are described using three categories of homebound status: homebound (never or rarely left home in the last month), semihomebound (left home with assistance, needed help or had difficulty), and nonhomebound (left home without help or difficulty). Results: In unadjusted analyses, 2‐year mortality was 40.3% in homebound participants, 21.3% in those who were semihomebound and 5.8% in those who were nonhomebound. Homebound status was associated with greater 2‐year mortality, adjusted for sociodemographic characteristics, comorbidities, and functional status (hazard ratio = 2.08; 95% confidence interval = 1.63–2.65, P < .001). Half of older community‐dwelling Medicare beneficiaries were homebound in the year before death. Conclusion: Homebound status is associated with greater risk of death independent of functional impairment and comorbidities. To improve outcomes for homebound older adults and the many older adults who will become homebound in the last year of life, providers and policymakers need to extend healthcare services from hospitals and clinics to the homes of vulnerable individuals.